A novel Faraday-cage inspired FSS shield for stable resonance performance characteristics. Issue 1 (2nd January 2020) - Krushna Kanth, V.; Raghavan, S.
ABSTRACT: In this letter, a novel Faraday cage inspired frequency selective surface (FSS) array is illustrated to patch-type periodic element. A metallic via has been used to stow the two patch conducting arrays printed on either side of the substrate. The intended application of the proposed electromagnetic (EM) structure is at microwave frequencies for improved bandwidth characteristics and stable resonance response. The structure shows a very stable resonance performance up to 60° oblique incident angle and 11.52% improvement in its fractional bandwidth. In addition, the simulation results of proposed design prove the validity of proposed structure for high microwave powers. Finally, the fabricated prototype along with experimental results of the Faraday cage array show the efficacy of proposed structural design.